Identification of stair climbing ability levels in community-dwelling older adults based on the geometric mean of stair ascent and descent speed: The GeMSS classifier. (January 2017) - Mayagoitia, Ruth E.; Harding, John; Kitchen, Sheila
Abstract: The aim was to develop a quantitative approach to identify three stair-climbing ability levels of older adults: no, somewhat and considerable difficulty. Timed-up-and-go test, six-minute-walk test, and Berg balance scale were used for statistical comparison to a new stair climbing ability classifier based on the geometric mean of stair speeds (GeMSS) in ascent and descent on a flight of eight stairs with a 28° pitch in the housing unit where the participants, 28 (16 women) urban older adults (62–94 years), lived. Ordinal logistic regression revealed the thresholds between the three ability levels for each functional test were more stringent than thresholds found in the literature to classify walking ability levels. Though a small study, the intermediate classifier shows promise of early identification of difficulties with stairs, in order to make timely preventative interventions. Further studies are necessary to obtain scaling factors for stairs with other pitches. Highlights: The geometric mean of speeds going up and down stairs (GeMSS) is easy to obtain. GeMSS related well statistically with functional tests especially the timed-up-and-go. GeMSS thresholds quantitatively separate three levels of stair climbing ability. GeMSS can help identify older adults before they can no longer climb stairs safely. GeMSS middle level may help detect stair climbing decline earlier than current tests.